Fungal communities in pressmud composting harbour beneficial and detrimental fungi for human welfare - de Oliveira, Tássio Brito [UNESP]; Lopes, Viviane Cristina Padilha [UNESP]; Barbosa, Fernando Nogueira [UNESP]; Ferro, Milene [UNESP]; Meirelles, Lucas Andrade [UNESP]; Sette, Lara Durães [UNESP]; Gomes, Eleni [UNESP]; Rodrigues, Andre [UNESP] (Microbiology Society, 2016)
Pressmud is a substrate derived from sugarcane juice filtrate, and around 26–40 kg of this residue are produced per ton of sugarcane. It is mainly used as fertilizer in crops, and its application in the field is often made without any prior treatment, but, in this research, it was studied for the risk this practice poses for human health. This research was stimulated by previous results indicating the presence of opportunistic pathogens in residues used in various composting systems and the extensive use of fresh pressmud in agriculture. Here, It was assessed the fungal diversity present in both fresh and composting pressmud using 454 pyrosequencing. In addition, heat-tolerant fungi were isolated and surveyed for their enzymatic repertoire of biomass-degrading enzymes (cellulase, xylanase, laccase and polygalacturonase). A wide range of opportunistic pathogens was found among the most abundant taxa in the fresh pressmud, such as Lomentospora prolificans (43.13 %), Trichosporon sp. (10.07 %), Candida tropicalis (7.91 %), and Hormographiella aspergillata (8.19 %). This indicates that fresh pressmud might be a putative source of human pathogenic fungi, presenting a potential threat to human health if applied as fertilizer without any treatment. With regard to the heat-tolerant fungi found in this substrate, all the 110 isolates screened were able to produce at least one of the tested enzymes. The pressmud composting process not only effectively reduces the load of pathogenic fungi, but also creates an interesting environment for fungi able to produce thermostable hydrolytic and oxidative enzymes with biotechnological applications.
Keywords: 454 pyrosequencing; Filter cake; Lignocellulose; Sugarcane; Thermophilic fungi